Effects of photobiomodulation and exercises on pain and muscle strength in knee osteoarthrosis: A systematic review (Research, Society and Development, 2021)
Introduction: Osteoartosis is a degenerative disease that may or may not be associated with inflammatory processes, one of the possible therapeutic resources for the treatment of this disease is laser photobiomodulation. Objectives: This study aims to analyze, through a systematic literature review, the effectiveness of photobiomodulation and exercises in pain and muscle strength in knee osteoarthritis. Methodology: A bibliographic survey was carried out in the Medline, PubMed and Scielo databases, using as descriptors: osteoarthritis, photobiomodulation, physiotherapy, laser therapy. 35 articles were identified with year of publication between 2011-2020, written in Portuguese and English. Subsequently, the abstracts of the articles were read, eliminating 29 articles that did not meet the criteria. Results: 6 articles comprised this review, demonstrated different infrared laser parameters, and different exercise protocols, but all with good results. Conclusion: it is concluded that the use of infrared laser photobiomodulation associated with strength training has great efficacy in the treatment of patients with knee osteoarthritis.